Disparate spinal and supraspinal opioid antinociceptive responses in β-endorphin-deficient mutant mice - Mogil, J. S. (2000)
The role of endogenous opioid systems in the analgesic response to exogenous opiates remains controversial. We previously reported that mice lacking the peptide neurotransmitter β-endorphin, although unable to produce opioid-mediated stress-induced antinociception, nevertheless displayed intact antinociception after systemic administration of the exogenous opiate morphine. Morphine administered by a peripheral route can activate opioid receptors in both the spinal cord and brain. However, β-endorphin neuronal projections are confined predominantly to supraspinal nociceptive nuclei. Therefore, we questioned whether the absence of β-endorphin would differentially affect antinociceptive responses depending on the route of opiate administration. Time- and dose-response curves were obtained in β-endorphin-deficient and matched wild-type C57BL/6 congenic control mice using the tail-immersion/withdrawal assay. Null mutant mice were found to be more sensitive to supraspinal (i.c.v.) injection of the μ-opioid receptor-selective agonists, morphine and D-Ala2-MePhe4-Gly-ol5 enkephalin. In contrast, the mutant mice were less sensitive to spinal (i.t.) injection of these same drugs. Quantitative receptor autoradiography revealed no differences between genotypes in the density of μ, δ, or κ opioid receptor binding sites in either the spinal cord or pain-relevant supraspinal areas.Thus we report that the absence of a putative endogenous ligand for the μ-opioid receptor results in opposite changes in morphine sensitivity between discrete areas of the nervous system, which are not simply caused by changes in opioid receptor expression.